Operational control and monitoring measures for water safety risks in the surface catchment of the Corumbataí River in the municipality of Rio Claro (SP) - Ferro, Luiz Henrique Rosolen; Ventura, Katia Sakihama; Vaz Filho, Paulo (National Journal of City Management, 2025)
Objective – Proposing measures to control and monitor contamination of the Corumbataí River source and surface catchment area, in the municipality of Rio Claro (SP). Methodology - The research was based on a bibliographic review and exploratory analysis of the study area with sustainability indicators and prioritization of the risk matrix to propose an improvement plan based on the recommendations of the World Health Organization and NBR 17080. Originality/relevance - The prioritization of risks to water contamination is a complementary element to the analysis of water quality. However, public managers do not adopt the Water Safety Plan (PSA) as a decision-making instrument for the management of water resources and local supply due to lack of knowledge of the requirements of Ministerial Ordinance 888/2021 or lack of commitment in public management to address the issue. The originality of the research consists in structuring a plan of measures based on dangerous events, identification of the degree of risk, objective of control, control measures and monitoring strategies. Results - Among the most aggressive hazardous events, the following stand out: the transport of contaminants by surface runoff; discharge of effluents due to tank cleaning; the existence of erosion and waste from mining operations; and the existence of septic tanks near the water intake. Sustainability indicators at unsatisfactory levels are more related to climate change than to water and sanitation, and climate resilience proves to be the weak link in this adaptation. Theoretical/methodological contributions - The adopted methodology had its subjectivity minimized by previous studies and field visits to collect primary data in the vicinity of the water intake, which is in a rural area. Social and environmental contributions – The main social and environmental indications refer to the need for reforestation and earthworks to control erosion, socio-environmental mobilization actions, water quality monitoring with discussion in society, changing the form of public management to adaptive and inclusive management, in addition to strengthening water governance as a unique criterion for the sustainability and resilience of cities.